2004
DOI: 10.1200/jco.2004.06.144
|View full text |Cite
|
Sign up to set email alerts
|

Benefit and Timing of Second Transplantations in Multiple Myeloma: Clinical Findings and Methodological Limitations in a European Group for Blood and Marrow Transplantation Registry Study

Abstract: To improve survival of tandem autologous transplantation in multiple myeloma, the second transplantation should preferably be performed before relapse and within 6 to 12 months of the first transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…In a retrospective study, Morris et al 12 showed that a second ASCT performed before relapse and within 6 to 12 months of the first ASCT improved survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Morris et al 12 showed that a second ASCT performed before relapse and within 6 to 12 months of the first ASCT improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Recently, a retrospective study has compared tandem ASCT up front with a strategy including planned second ASCT at relapse or progression. 12 In this retrospective study, Morris et al 12 showed that a second ASCT performed before relapse and within 6 to 12 months of the first ASCT improved survival.…”
Section: Introductionmentioning
confidence: 93%
“…23 The complete remission rates in patients with this type of myeloma appear to be very high, both before and after transplantation, possibly because of the lack of an identifiable paraprotein. The progression-free survival of patients with non-secretory myeloma appears to be superior to that of patients with common myeloma (P=0.0003), but there was no difference in overall survival between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis by the EBMT registry suggested that the completion of a second HSCT before relapse and within 6-12 months of the first transplant resulted in superior outcomes. 94 The Arkansas group performed serial landmark analyses to define the optimal timing of a planned HSCT in TTI: 79 EFS and OS both were longer among the patients who had received a second HSCT within 12 months. Cure of multiple myeloma P Hari et al Cure and 'operational cure' There are no studies that demonstrate a plateau in the relapse curve for MM patients undergoing intense HDT.…”
Section: Benefits Of Tandem Transplantationmentioning
confidence: 99%